Incus Necrosis and Blood Supply: A Micro-CT and Synchrotron Imaging Study. Issue 7 (August 2019) - Enghag, Sara; Strömbäck, Karin; Li, Hao; Rohani, Seyed Alireza; Ladak, Hanif M.; Rask-Andersen, Helge; Agrawal, Sumit
Abstract : Background: Incus necrosis is a common complication following stapes surgery and is associated with impaired microcirculation. The objective of this study was to investigate the vascular anatomy of the human incus by using light microscopy, micro-computed tomography (micro-CT), and synchrotron phase-contrast imaging (SR-PCI) for a novel three-dimensional (3D) analysis of the middle ear, mucosal folds, major vascular pathways, and intraosseous vascular bone channels. Methods: One-hundred-and-fifty temporal bones from the Uppsala collection were analyzed under light microscopy. Twenty temporal bones underwent high-resolution micro-CT scanning, and an additional seven specimens underwent SR-PCI at the Canadian Lightsource in Saskatoon, Canada. One of these specimens was from an individual who had undergone stapes surgery. Data were processed with volume-rendering software to create 3D reconstructions using scalar opacity mapping for bone transparency, cropping, and soft tissue analyses. Results: Micro-CT and SR-PCI with 3D rendering revealed the extensive vascular plexus within the un-decalcified incus bone communicating with the exterior surface. The relationship between the vessels, lenticular process, and incudostapedial joint were clearly observed. SR-PCI allowed for histologic-level detail while preserving the specimen and its 3D relationships. Conclusion: SR-PCI with 3D reconstructions confirmed the main vascular supply to the lenticular process along the intraosseous lenticular vessels. This is the first synchrotron analysis of a patient having undergone stapes surgery, and it suggests that incus necrosis associated with stapes surgery may be caused by a disruption of the lenticular blood flow induced by the prosthesis loop, and not by strangulation of mucosal vessels as has been previously described. Abstract : Supplemental Digital Content is available in the text